An interview with Professor Emeritus Brenda Dervin. Issue 3 (27th May 2021) - Kelly, Matthew
Abstract: In 2019, Professor Emeritus Brenda Dervin agreed to participate in a series of interviews to discuss her life and work. Two sessions were conducted with Dervin that covered scholarly and biographical topics. The interviews reveal aspects of Dervin's personal journey as a researcher, and a teacher, and provide insight into how she saw the related fields of information science and communication developing shared interests and shared perspectives in social research. Dervin candidly shares how her life experiences, both inside and outside of academia, have influenced the development of her theoretical approach. Readers will find here discussion of a range of issues associated with the Sense-Making Methodology as well as Dervin's thoughts on how information and communication domains intersect within the context of modern digital environments. With reference to her own experiences, Dervin outlines how important it is to ensure that leadership within complex online environments is fostered in the areas of public information provision, and in civic dialogue, and how managing the information frameworks within which critical inquiry can thrive requires increasing commitment to, and understanding of, the human-centered considerations surrounding interpretation and identity. Further information on Dervin can be found at Bonnie Cheuk's site: www.sense-making.org .